Antitumor effect of Bothrops jararaca venom - da Silva, R. J.; da Silva, M. G.; Vilela, L. C.; Fecchio, D. (Carfax Publishing, 2002)
MANY experimental studies have been carried out using snake venoms for the treatment of animal tumors, with controversial results. While some authors have reported an antitumor effect of treatment with specific snake venom fractions, others have reported no effects after this treatment. The aim of this study was to evaluate the effect of Bothrops jararaca venom (BjV) on Ehrlich ascites tumor (EAT) cells in vivo and in vitro. In the in vivo study, Swiss mice were inoculated with EAT cells by the intraperitoneal (i.p.) route and treated with BjV venom (0.4 mg/kg, i.p.), on the 1st, 4th, 7th, 10th, and 13th days. Mice were evaluated for total and differential cells number on the 2nd, 5th, 8th, 11th and 14th days. The survival time was also evaluated after 60 days of tumor growth. In the in vitro study, EAT and normal peritoneal cells were cultivated in the presence of different BjV concentrations (2.5, 5.0, 10.0, 20.0, 40.0, and 80 mug) and viability was verified after 3, 6, 12 and 24 h of cultivation. Results were analyzed statistically by the Kruskal-Wallis and Tukey tests at the 5% level of significance. It was observed that in vivo treatment with BjV induced tumor growth inhibition, increased animal survival time, decreased mortality, increased the influx of polymorphonuclear leukocytes on the early stages of tumor growth, and did not affect the mononuclear cells number. In vitro treatment with BjV produced a dose-dependent toxic effect on EAT and peritoneal cells, with higher effects against peritoneal cells. Taken together, our results demonstrate that BjV has an important antitumor effect. This is the first report showing this in vivo effect for this venom.
Keywords: antitumor effect; Ehrlich ascites tumor; Bothrops jararaca; venom